High CTC-TRPC5 Expression Significantly Associated With Poor Prognosis in Radical Resected Colorectal Cancer Patients - Cai, Dongyan; Li, Na; Jin, Linfang; Qi, Xiaowei; Hua, Dong; Wang, Teng (Frontiers in Molecular Biosciences, 2021)
Recurrence is the main reason of treatment failure of redical resected colorectal cancer (CRC). Although some factors including staging and differentiation have been proven to useful for recurrence evaluation, prognosis of certain patients does not conform to this evaluation approach. Circulating tumor cells (CTC) have been found to have prognostic value in CRC, and previous studies on CTC have primarily focused on their numbers. CTC are functionally heterogeneous cell populations, and different CTC subgroups may have different functions and clinical values. In our previous study, we discovered that elevated expression of the transient receptor potential channel TRPC5 was associated with a significantly poor prognosis in CRC. In this study, we collected peripheral blood from CTC-positive CRC patients, identified the TRPC5 protein expression on CTC (CTC-TRPC5), and analyzed the relationship between CTC-TRPC5 expression levels and the prognosis. The results showed that CTC-TRPC5 level is significantly related to the T stage and differentiation of tumors. High level of CTC-TRPC5 is more common in a high T stage as well as poorly differentiated tumors and is significantly associated with shorter disease free survival (DFS). The median DFS of CRC patients with high and low CTC-TRPC5 level was 17.1 months and 22.0 months, respectively (P<0.05). This study revealed a clinically significant CTC subgroup of CRC, providing a new indicator for clinical evaluation of CRC prognosis.